Advances in delay-tolerant networks (dtns) architecture and enhanced performance - Rodrigues, Joel 1972- (Elsevier, 2015)
Part one looks at delay-tolerant network architectures and platforms including DTN for satellite communications and deep-space communications, underwater networks, networks in developing countries, vehicular networks and emergency communications. Part two covers delay-tolerant network routing, including issues such as congestion control, naming, addressing and interoperability. Part three explores services and applications in delay-tolerant networks, such as web browsing, social networking and data streaming. Part four discusses enhancing the performance, reliability, privacy and security of delay-tolerant networks. Chapters cover resource sharing, simulation and modeling and testbeds
Includes bibliographical references and index
Keywords: COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Computer networks; Computer networks / Reliability; Fault-tolerant computing; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Computer networks -- Reliability